2013
DOI: 10.11118/beskyd201306010043
|View full text |Cite
|
Sign up to set email alerts
|

Growth under elevated CO2 concentration affects the temperature response of photosynthetic rate

Abstract: In this study, we tested the hypothesis that an elevated CO2 concentration leads to a shift of the temperature optimum of the photosynthetic rate in trees. Since the elevated CO2 treatment usually leads to a significant decrease in stomatal conductance and consequently to decrease in transpiration followed by an increase in leaf temperature, we hypothesized that elevated CO2 results in the acclimation of photosynthetic apparatus to the higher temperature.We studied the two most common species in the Czech Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moreover, Holišová et al . ( 2013 ) showed that beech has an optimal foliar temperature of about 24.5°C for A sat . We observed a mean air temperature of around 29°C between 09:00 and 16:00 h in the middle of the growing season (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Holišová et al . ( 2013 ) showed that beech has an optimal foliar temperature of about 24.5°C for A sat . We observed a mean air temperature of around 29°C between 09:00 and 16:00 h in the middle of the growing season (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…S2 ), suggesting that trees grown at warmer temperatures tended to acclimate for the optimum temperature of J max and V c max (Kattge & Knorr, 2007 ). Overall, our findings suggest that beech will suffer from a warming atmosphere (Šimpraga et al ., 2011 ; Holišová et al ., 2013 ), while oak may benefit from temperature rise in temperate climates where heat stress is not yet limiting this species (Arend et al ., 2013 ; Kuster et al ., 2014 ). As shown in our study, photosynthetic responses to chronic warming are highly dependent of local climatic conditions and species' origin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, variations in these responses depend on species-specific sensitivity to temperature. Beech typically grows in a mild climate and has a T opt around 24.5 °C ( Holišová et al 2013 ) whereas downy oak ( Quercus pubescens Willd.) usually grows in Mediterranean areas with a T opt of about 26 °C ( Ilnitsky et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%